IDYLL 7 AND THE HYMN TO HERMES. (29th June 2015) - Rudoni, Elia R.
Abstract : Simichidas' self-presentation as a poet at Theocritus 7.37 is modelled on Apollo's self-presentation as a musician at Homeric Hymn to Hermes 450. Through this allusion, in his own Dichterweihe as a bucolic poet Simichidas hints at the invention of the bucolic genre by Hermes. The reference is crafted so as to point self-reflexively to its status as reference; in particular, the expression καὶ γὰρ ἐγώ ('I too') of line 37 functions as an intertextual signpost. If Simichidas is a literary projection of Theocritus, the allusion has important implications for our understanding of his self-positioning within the poetical tradition.